Análise de um sistema fotovoltaico para suprimento de energia elétrica em uma escola municipal indígena na zona ribeirinha em plena região amazônica - Santos, Lucas Andrey dos (Brasil, 2022)
It is evident in Brazil that the energy crisis is a serious feature in terms of preserving the environment and the use of non-renewable energy and with that Brazil's concern to diversify the energy matrix, observing as the main composition of electric energy generation. The use of photovoltaic systems is of great incidence and great potential in the country, which is considered a territory of abundance in solar radiation. This Course Completion Work (TCC) is being important in the face of the problem and the universe of electric energy that is considered scarce due to the problems of logistics and facing bureaucracy in relation to the riverside indigenous communities within a historical and cultural context. The work is a case study and a specific analysis of the technical-economic feasibility of the implementation of a voltage system at the elementary level Kanata T-Ykua Municipal School, located in the Três Unidos Indigenous Community, in the riverside area of Rio Negro in the city of Manaus/AM.E with the objective of supplying the electric energy demand of the aforementioned school. The results were beneficial and positive in terms of cost-effectiveness and its payback time in years of useful life of a photovoltaic system that, in addition to recovering the initial investment in 8 years after its implementation and with the lifetime cost of solar panels of 25 years, generating an energy credit for the education department that the school demands.